Lipid-engineered nanotherapeutics for cancer management - Fernandez-Fernandez, Alicia; Manchanda, Romila; Kumari, Manisha (Frontiers in Pharmacology, 2023)
Cancer causes significant mortality and morbidity worldwide, but existing pharmacological treatments are greatly limited by the inherent heterogeneity of cancer as a disease, as well as the unsatisfactory efficacy and specificity of therapeutic drugs. Biopharmaceutical barriers such as low permeability and poor water solubility, along with the absence of active targeting capabilities, often result in suboptimal clinical results. The difficulty of successfully reaching and destroying tumor cells is also often compounded with undesirable impacts on healthy tissue, including off-target effects and high toxicity, which further impair the ability to effectively manage the disease and optimize patient outcomes. However, in the last few decades, the development of nanotherapeutics has allowed for the use of rational design in order to maximize therapeutic success. Advances in the fabrication of nano-sized delivery systems, coupled with a variety of surface engineering strategies to promote customization, have resulted in promising approaches for targeted, site-specific drug delivery with fewer unwanted effects and better therapeutic efficacy. These nano systems have been able to overcome some of the challenges of conventional drug delivery related to pharmacokinetics, biodistribution, and target specificity. In particular, lipid-based nanosystems have been extensively explored due to their high biocompatibility, versatility, and adaptability. Lipid-based approaches to cancer treatment are varied and diverse, including liposomal therapeutics, lipidic nanoemulsions, solid lipid nanoparticles, nanostructured lipidic carriers, lipid-polymer nanohybrids, and supramolecular nanolipidic structures. This review aims to provide an overview of the use of diverse formulations of lipid-engineered nanotherapeutics for cancer and current challenges in the field.